(untitled) (Journal of the Sylhet Agricultural University, 2025)
The study aimed to improve the nutritional quality of poultry feed through whey fermentation. Whey, a by-product of the cheese industry rich in high-quality proteins, was incorporated into feed ingredients such as maize, wheat bran, soybean meal and auto rice polish. Sweet whey fermented by lactic acid bacteria was used in five different treatments: Control T0 (without whey), T1 (20 ml whey/100g feed), T2 (30 ml whey/100g feed), T3 (40 ml whey/100g feed), and T4 (50 ml whey/100g feed), incubated for 24, 48, and 72 hours in a 5x3 factorial design. Proximate analyses revealed significant nutritional improvements in the whey-fermented feeds. The results indicated that the optimal crude protein (CP) content was achieved in soybean meal at T3 (45.41%) and wheat bran at T1 (16.88%) after 72 hours. Crude fiber (CF) content decreased significantly, with T4 showing the lowest CF values across various feed types, enhancing digestibility. Ether extract (EE) and total ash content varied, with notable EE increases at T4 treatments. The study concluded that whey fermentation significantly enhances the protein content and digestibility in poultry feed with varying impacts on other nutritional components with 40 ml whey/100g feed for 72 hours incubation being the most effective treatment, suggesting a practical approach to improving poultry nutrition and production performance. This research provides a viable strategy for utilizing whey, contributing to the sustainable development of the poultry sector in Bangladesh. J. Sylhet Agril. Univ. 11(1): 31-36, 2024